The influence of board independence, competency and ownership on earnings management in Malaysia - Johari N.H.; Saleh N.M.; Jaffar R.; Hassan M.S. (2023)
This paper examines the roles of independent members on the board, chief executive officer who also serves as a chairman of the company, board competency and management's share ownership on earnings management practices. Different from prior research, it also investigates whether independent board competency (an interaction of independence and competency) and independent board share ownership (an interaction of independence and management ownership) would lead to better monitoring over earnings management. It also examines whether board competency and share ownership could compensate the missing role of monitoring when CEO duality exists. The results indicate that excessive shareholding beyond 25% by managers may induce managers to manage earnings, and a combined chairman-CEO roles (CEO duality) does not influence the practice of earning management in Malaysian firms. The results also indicate that the minimum composition of one-third independent director, as suggested by the Code of Corporate Governance in Malaysia is not adequate to monitor the management from earnings management practices.